2014
DOI: 10.4028/www.scientific.net/amr.941-944.825
|View full text |Cite
|
Sign up to set email alerts
|

Modern Building Materials and the Concept of "Sustainability Project"

Abstract: The term "sustainable development" came in to use in 20th century and can be regarded as the set of mind notion. The International Union of Architects by the Copenhagen Declaration (December 7th, 2009), noted that "the concept of sustainability project" recognizes that all architectural and urban objects are part of a complex interactive system linked to their natural environment" [1]. The search for modern energy efficient building materials and technologies should be linked to the energy-efficient landscapin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Authors of the thesis [2] claim that nevertheless "even with a growth of average security with housing, the share of the people having housing of "low" quality doesn't decrease". Really, such problem has a wide circulation in the territory of St. Petersburg, but by sight authors of this article can be found the ways allowing "to go to a meeting" to the population, having reduced housing cost, for example, by means of cooperation of government bodies and commercial banks to present the most favorable conditions for receiving a mortgage in the new building, for example, to young families [6][7][8][9].…”
Section: Sequence Of Implementation Of Renovationmentioning
confidence: 99%
“…Authors of the thesis [2] claim that nevertheless "even with a growth of average security with housing, the share of the people having housing of "low" quality doesn't decrease". Really, such problem has a wide circulation in the territory of St. Petersburg, but by sight authors of this article can be found the ways allowing "to go to a meeting" to the population, having reduced housing cost, for example, by means of cooperation of government bodies and commercial banks to present the most favorable conditions for receiving a mortgage in the new building, for example, to young families [6][7][8][9].…”
Section: Sequence Of Implementation Of Renovationmentioning
confidence: 99%
“…The construction industry is one of the largest users of energy, material resources, and water which is a formidable polluter (Horvath, 2004), it is also consumed approximately 50% of all global resources, representing six billion tons of industrial raw materials each year (Augenbroe et al, 1998;Edwards and Hyeyy, 2005). The term "sustainable development" came into use in the 20th century (Gayevskaya and Rakova, 2014). Environmental building performance assessment is one of the major issues in sustainable construction (Cole, 1998;Cooper, 1999;Holmes & Hudson, 2000), at a stage even before a design is conceptualized (Ding, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Bakhoum et al (2015) stated that in the construction industry, the selection of sustainable construction materials during the design phase leads to a move towards more sustainable construction. Modern construction materials must provide durable exploitation of energy-efficient objects (Gayevskaya and Rakova, 2014). The greater the material's durability, the lower the time and resources required to maintain it (de Silva et al, 2004;Caffi and Rejna, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The primary task of the facade is to protect the building from weather, temperature extremes, drafts, heat loss [1][2][3][4][5][6][7][8]. The economy of energy resources is considered by the developed countries as the major national environmental and economic issue because of energy saving measures higher profitability and environmental safety than increasing energy resources [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%